Findbuch des Bestandes Abt. 47.1: Kuratorium der Christian-Albrechts-Universität Kiel - Asmussen, Georg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2007)
The available files of the University Board of Trustees are not a unified old registry that has been taken over by one single institution, but rather created by merging smaller and larger groups of files which, depending on the chronological classification of the board of trustees into the administration, were found in different records.